Embracing the metaverse: a survey of virtual reality and augmented reality practices at the United States’ top one hundred university libraries - Guo, Yajun; Li, Shuai; Zhang, Xindi; Fu, Yiyang; Yuan, Yiming; Liu, Yanquan (College & Research Libraries, 2024)
The purpose of this study is to learn more about virtual reality (VR) and augmented reality (AR) practices at the United States’ top one hundred university libraries, as well as how they are engaging with the metaverse. We conducted qualitative and descriptive analysis on the websites of the top one hundred university libraries in the United States to determine the application fields and application proportions of VR and AR technologies and found good practice examples of using VR and AR technologies in this field. The findings show that 86 percent of the top one hundred US university libraries have implemented VR and AR technologies, with practice areas focused on: VR/AR studio and VR/AR makerspace; immersive learning services and virtual exhibitions/conference services; visual geographic information system and VR navigation services; virtual reading services and visual retrieval services; and VR reference services. The study provides university library administrators and professionals with the most up-to-date information and best practices of VR and AR engagement areas and the proportion of use, which can aid in the development of strategies to leverage VR and AR technologies to improve patron service and embrace the metaverse for the communities they serve.
Keywords: Metaverse；Virtual reality；Augmented reality；University Library；America；Survey; dept.ils; peer-reviewed

Role of Pakistani e-libraries in promoting health awareness for the attainment of Sustainable Development Goal-3 - Soroya, S.H.; Sharif, A.; Faiola, A. (Health Information and Libraries Journal, 2024)
Background: Pakistan is a densely populated South Asian country. It is facing numerous health challenges, as well as problems of the digital divide. The government of Pakistan established e-libraries as a pilot project in 2018. These libraries are functioning through community centers/public libraries in the largest province of the country. Objective: This paper examines the role of Pakistani e-libraries in creating health awareness and providing health information to the public. Methods: The qualitative research design was based on focus group discussions with the head librarians of all 13 of the 20 e-libraries contacted. Results: The findings revealed that e-libraries actively create health-related awareness and connect the public to health advisors. The e-libraries were engaged in four types of health-related activities (seminars, awareness campaigns, open health camps, and special health day celebrations) with high attendance from the public. Attendees of these programs returned to librarians with additional health-related queries. Conclusions: The study suggests a need for more liaison between the community and local healthcare institutions. This approach can make these programs more effective in helping individuals manage their health. The results of this study can serve as a useful guide for other developing nations in developing similar services. © 2024 Health Libraries Group.
Keywords: Asia; dept.ils; developing economies; digital information resources; health disparities; information services; peer-reviewed; public health; public libraries; south

Readiness of Pakistani journals for open access publishing - Raza, M.Z.; Rafiq, M.; Soroya, S.H. (Electronic Library, 2024)
Purpose: This study was designed to discover the readiness of the higher education commission (HEC)-recognized journals of Pakistan in terms of human, financial and technological resources, technical expertise, institutional support, availability of open access (OA) policy, availability of guidance and training, willingness, motivation and so on for OA journal publishing and to expose the challenges in OA journal publishing. Design/methodology/approach: A quantitative research approach was used and a structured questionnaire was developed to meet the objectives of this study. A survey method was used to collect data from the editors of all 329 HEC-recognized journals in Pakistan. Findings: The respondents of all the HEC-recognized journals of Pakistan are neutral and are not of the view that they have sufficient financial, human, technological/infrastructural resources and technical expertise to continue/initiate an OA journal publishing. ‘No academic reward’; and ‘no monetary reward for the editorial staff’ are both enormous challenges for OA journal publishing. The perceived challenges of OA have a negative impact on readiness for OA publishing. The readiness level of the respondents of the OA journals is higher as compared to the readiness level of the respondents of non-OA journals. Research limitations/implications: This study covered the lists of HEC-recognized journals of 2019. More studies may be conducted based on updated lists of HEC-recognized journals. Qualitative studies may also be conducted to discover the readiness of the HEC-recognized journals of Pakistan for OA journal publishing. Originality/value: This study is the first comprehensive study on this phenomenon and is an effort to fill this gap to invigorate scholarly literature. It may attract the attention of policymakers, funding bodies, parent institutions of the journals and the HEC regarding the readiness of journals in terms of financial, human, technological/infrastructural resources, technical expertise of the journals and challenges of journals to prompt the OA journal publishing paradigm. © 2024, Emerald Publishing Limited.
Keywords: Challenges; Editors; Journal publishing; Journals; Open access; Pakistan; Readiness; dept.ils

Exploring the nexus: homeschooling and library engagement in Connecticut - Murtha, Helene R.; Schofield, Cindy K. (Public Library Quarterly, 2024)
In the dynamic landscape of education, homeschooling continues to offer a compelling alternative to traditional schooling. Homeschool numbers surged through the pandemic and have not decreased to pre-pandemic levels. This study examines the shared connections between homeschooled families in Connecticut and local public libraries by looking at how home educators use library resources and participate in library programming; and examining how Connecticut libraries perceive and respond to the diverse needs of homeschooling communities. Based on 2 Connecticut statewide surveys, one sent to public librarians and another to homeschoolers, the study sought to identify areas of strengths, weaknesses and disconnects in the homeschool community and public library relationships in Connecticut. Both qualitative and quantitative data was collected and reviewed to identify potential improvements to the evolving role of libraries in supporting alternative education pathways, and the potential for an infusion of public library support from the homeschool community.
Keywords: Homeschooling; dept.ils; education resources; libraries; peer-reviewed; public libraries; special populations

ADA digital accessibility on academic library websites - Liu, Yan Quan; Bielefield, Arlene; Beckwith, Jennifer (College & Research Libraries, 2024)
Studying ADA accessibility at library websites of top universities selected from the U.S. News and World Report, the authors used WAVE and AChecker to assess data in compliance with WCAG 2.0 standards. Almost 8 out of 10 public university academic libraries reported accessibility errors as one of the major findings. Low color contrast was becoming a more commonly occurring accessibility issue, making it difficult for people with vision impairments to perceive the color of the image. The outcomes of the study suggest that academic libraries around the world should continue improving their website accessibility.
Keywords: SCSU-student; dept.ils; peer-reviewed

Assessing the impact of health information orientation and health information literacy on patients’ engagement with health information - Hashmi, Ferhana Saeed; Soroya, Saira Hanif; Mahmood, Khalid (Journal of Information Science, 2024)
Health information engagement can help individuals to find and use reliable sources of health information to make informed decisions about their health. This helps to improve their health outcomes and prevent unnecessary healthcare costs. Drawing upon the cognitive behavioural theory, this pilot study postulated a model to understand that the consequences of information orientation in terms of information engagement (behaviour), information literacy (cognition) and information avoidance (behaviour) in post-COVID era under health context. Furthermore, the moderation effects of health information literacy (HIL) are also calculated in managing health information avoidance beahvior. This pilot study is conducted in the context of social media exposure to health information by diabetic patients in Pakistani community. The proposed model was tested using Partial Lease Square Structural Equational Modelling (PLS-SEM). The data were collected from 166 diabetic patients (active social media users) through a survey. The study findings suggest that health information orientation on social media leads to HIL and engagement. Whereas, it has significant negative impact towards health information avoidance behaviour. Furthermore, HIL significantly increases health information engagement of diabetic patients. Also, HIL moderates the relationship between health information orientation and information engagement positively, whereas between health information orientation and health information avoidance negatively.
Keywords: dept.ils; peer-reviewed